Modelo para tomada de decisão em programas de eficiência energética no setor de distribuição de eletricidade - SILVA, Rogério Diogne de Souza e (Universidade Federal do Pará, 2018)
The electricity distribution system is constantly evolving, with the dissemination of distributed energy resources, smart grids and the inclusion of competitive markets, in which the use of energy efficiency as a relevant resource for sector planning must be ensured through public policy. Brazil has for decades had a program and policy in this area, however, the results of its program for the insertion of energy efficiency actions with the financial resources of the electricity utilities, have less impact than similar programs in other countries, and there is the imminent need to meet the emission reduction targets proposed by the country at the 21st Conference of the Parties of the United Nations in December 2015 in Paris. In this context, the present thesis proposes the development of a non-parametric model for the determination of performance indicators and classification of energy efficiency projects. It also contributes to the evaluation of the Energy Efficiency Program, through a methodology to analyze the projects, classify and quantify the variables, resulting in recommendations for the improvement of the program. A database of projects submitted to ANEEL by the utilities of the electricity distribution sector from 2008 to 2016 was used. The model was developed using Data Envelopment Analysis (DEA), a non-parametric method that uses linear programming to calculate the most efficient units in a given set of decision-making units. The results show that the best performance was achieved by projects in the industrial and cogeneration categories, however, these constitute only 4.24 % of the projects presented and 5.28 % of the total investments in the last eight years, indicating the need to review energy efficiency regulatory strategies. As a solution to improve the selection of the best performing projects, it is suggested assigning weights to the categories to optimize the project results, by incentives to the projects with the best performance, without excluding the participation of all others, simply by providing energy savings goals and demand reduction at peak hours compatible with the best performing categories.